(untitled) (Indonesian Minority Justice Review, 2024)
This paper evaluates the effectiveness of Indonesia’s legal aid system in providing access to justice for marginalized groups, particularly ethnic, religious, and sexual minorities. Legal aid is a critical component of ensuring equal access to justice, yet marginalized communities often face challenges in navigating the legal system due to poverty, illiteracy, and discrimination. The study examines Indonesia’s legal aid framework, focusing on the 2011 Law on Legal Aid and its implementation through government and non-governmental organizations. Through interviews with legal aid providers, marginalized individuals, and human rights advocates, the research assesses the accessibility, quality, and impact of legal aid services on minority communities. The findings suggest that while legal aid has provided essential support for many disadvantaged individuals, there remain significant gaps in coverage, particularly in remote areas and for non-citizens, such as refugees. The paper concludes by proposing recommendations to enhance the legal aid system, including expanding funding, improving outreach to underserved communities, and strengthening partnerships between government and civil society to ensure broader access to justice for all.